2017
DOI: 10.1016/j.cyto.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamized ethyl alcohol improves immune response and behavior in murine infection with Trypanosoma cruzi

Abstract: The results demonstrate the beneficial effect of Ethylicum 6cH in acute murine infection by T. cruzi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…According to Sandri et al, potentized alcohol cannot be considered as an inert vehicle, but a specific homeopathic medicine, thus a comparative substance. 68 This is part of an adaptation process used by Artemia spp., called "diapause", to preserve the species when exposed to environmental stressful stimuli, in which there is arrest of embryo development at the gastrula stage, keeping a low metabolic level. These events are controlled by the expression of specific genes, mainly those related to the composition of the cyst wall, allowing the deposition of trehalose, a disaccharide that cannot be decomposed to glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sandri et al, potentized alcohol cannot be considered as an inert vehicle, but a specific homeopathic medicine, thus a comparative substance. 68 This is part of an adaptation process used by Artemia spp., called "diapause", to preserve the species when exposed to environmental stressful stimuli, in which there is arrest of embryo development at the gastrula stage, keeping a low metabolic level. These events are controlled by the expression of specific genes, mainly those related to the composition of the cyst wall, allowing the deposition of trehalose, a disaccharide that cannot be decomposed to glucose.…”
Section: Discussionmentioning
confidence: 99%
“…This sugar forms H bonds with proteins and phospholipids, forming a kind of bioglass, in a process called vitrification, allowing the maintenance of internal stability. 54,60,[67][68][69][70][71][72][73] Besides this first adaptative level of hatching reduction, another deeper level of hatching inhibition was revealed after the analysis of the whole population, independent of time and moon phase, with high statistical significance and large effect size against the controls, as observed after treatment with MC 30cH (►Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…56 In addition, some authors reported specific effects of potentized alcohol in experimental models in vitro by comparison to other Homeopathy controls. 57,58 Therefore, potentized alcohol seems to be more of a comparator than a negative control. Non-potentized alcohol may be used instead, or together with succussed water.…”
Section: Discussionmentioning
confidence: 99%
“…First, even in the absence of drugs, ultra-dilutions are expected to show some medicinal activities (non-specific immunotherapy) because immunomodulatory microbial lysates are always formed during preparation of homeopathic dilutions and they should be available in the homeopathic medicines irrespective of the availability of the drugs. Indeed, it has been reported that homeopathically potentized ethanol (equivalently, blank dilutions without drugs, as ethanol is a component of the homeopathic drug-vehicle) can enhance immune response in murine infection with Trypanosoma cruzi [68].…”
Section: How Can Ultra-diluted Medicines Devoid Of Drugs Show Therape...mentioning
confidence: 99%